Partnerships between community corrections and researchers: the view from the probation/parole chiefs - Kim, Bitna (Journal of crime and justice, 2022)
Calls to improve the interaction between academics and practitioners have been repeatedly pronounced by scholars and government leaders alike. A number of publications have focused on examining the experience and views of police leaders on partnerships with researchers. However, there is a general lack of knowledge about community corrections leaders’ receptivity to research and the experience and view of research partnerships. Our study addressed this limitation with a statewide survey of probation/parole chiefs in Pennsylvania. Guided by prior research on research partnerships in policing, the survey in the current project included questions about potential correlates of researcher-practitioner partnerships in addition to the questions measuring the experience and opinions of probation/parole chiefs in Pennsylvania on such partnerships. The current research results provide greater insight to inform practitioners and researchers on how to encourage the research utilization and tailor researcher-practitioner partnerships to the context and conditions within community corrections.